Flow characteristics of aluminium oxide nanofluids - Egan, V; Walsh, P; Walsh, E (2009)
The current study is an investigation in the flow characteristics of aluminium oxide nanofluids. Relative viscosity measurements are obtained for varying volume fractions using both a rotational viscometer and an experimental setup designed for pressure drop measurements in tubes. The effect of nanoparticle size and preparation method is also investigated as predispersed nanofluids of nominal particle size 10nm and 50nm are compared with each other and with a fluid mixed from Al2O3 nanopowder. Volume fractions of between 1% and 7% were tested. The first method employed to obtain viscosities is based on the Hagen-Poiseuille equation for laminar pipe flow, where pressure drop measurement and flow rate measurements are used to determine relative viscosities of various nanofluids samples. Viscosity measurements were also obtained for a number of solutions on a rotational viscometer and compared to the latter and existing models available in the literature. Overall, it was found during experimentation that the relationship between pressure and flow rate for the various nanofluids was linear indicating that the fluids were Newtonian in nature. An increase in viscosity was recorded for increasing volume fraction; however this was seen to be negligible for volume fractions lower than 1%. Overall it was also seen that both methods of determining relative viscosity were in good agreement. There was not a clear indication of the effect of nanoparticle size on the relative viscosity however the nanofluids formulated from purchased Al2O3 powder resulted in a considerably lower relative viscosity when compared to both nanofluids purchased pre-dispersed from suppliers. Copyright © 2009 by ASME.